The additive effect of esketamine and clonidine in patients at high risk for acute postoperative pain undergoing laparoscopic surgery: A randomised controlled trial - Mogianos, Krister ; 0009-0009-0622-990X; Holgersson, Josefine; Undén, Johan; Persson, Anna KM ; 0000-0002-9000-849X (Journal of Clinical Anesthesia, 2025)
Objective To evaluate if adding esketamine and clonidine has positive effects on postoperative pain, postoperative nausea and vomiting, and quality of recovery in patients who are at high risk for postoperative pain. Design Patient- and assessor-blinded, superiority, randomised controlled trial. Setting Single centre between 2022 and 2024. Patients 125 adult patients, ASA I – II, planned for elective laparoscopic surgery and risk-classified as high risk of pain, based on perceived pain associated with venous cannulation. Intervention Patients were randomised to either an anaesthesia protocol, including an intravenous bolus of esketamine (0.25 mg.kg−1) after induction and clonidine (1 μg.kg−1) during maintenance phase (EC), or standard of care (SOC) no esketamine or clonidine included. Measurements Primary outcome: worst pain intensity in the PACU. Secondary outcomes: worst pain, and proportion having NRS ≥ 4, at 24 h (during rest and movement), worst pain and proportion having NRS ≥ 1, at 3- and 6-months (during rest and movement), postoperative recovery at 24 h, PONV in the PACU and at 24 h. Rescue dose opioids in the PACU was an exploratory outcome. Results Worst pain scores in the PACU were 5.7 in the EC group and 5.5 in SOC group (P = 0.78). After 24 h, no difference in postoperative pain (rest; 5.8 vs 6.1, P = 0.35, movement; 6.1 vs 6.2, P = 0.68), postoperative recovery (P = 0.92) or PONV (P = 0.80) was found. Proportion of patients with NRS ≥ 4 in the PACU was 50 % vs 48 % (P = 0.55) and at 24 h 73 % vs 81 % at rest (P = 0.27) and 76 % vs 81 % during movement (P = 0.50). Rescue opioids in the PACU were similar (5.9 mg vs 6.6 mg, P = 0.47). There were no differences in persistent pain at 3 or 6 months at rest (P = 0.72, P = 0.12) or movement (P = 0.48, P = 0.18). Conclusion Adding esketamine and clonidine, as an individualised multimodal anaesthesia strategy, did not influence acute or persistent postoperative pain, early recovery, need of rescue opioids or PONV in patients, who were assessed as high risk for APOP.